Plated carbon material and method of manufacturing the same
By supporting particulate electroless plating catalysts and metal fine particles on carbon fibers and using an electroless plating method, the plated carbon material achieves enhanced deposition properties and uniformity, addressing the limitations of conventional methods and resulting in improved conductivity and performance.
Patent Information
- Application Number
- JP2023165262
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-04-08
AI Technical Summary
Conventional methods for producing plated fibers face challenges in achieving uniform metal plating due to insufficient deposition properties, which affects the conductivity and performance of the final material.
The development of a plated carbon material that includes carbon fibers or organic fibers with a particulate electroless plating catalyst and metal fine particles supported on the surface, followed by an electroless plating method to form a metal plating layer, thereby enhancing the deposition property and uniformity of the metal plating.
This approach results in a plated carbon material with improved conductivity and uniform metal plating, suitable for use as a conductive material and electromagnetic shielding material.
Smart Images

Figure 2025055859000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a plated carbon material and a method for producing the same. [Background technology]
[0002] In recent years, there has been a demand for conductive materials and electromagnetic shielding materials with a high degree of freedom in design, such as space saving, to ensure the stable operation of electronic devices. For this reason, the development of flexible conductive materials that are soft, lightweight, and bendable has been widely promoted. One such conductive material is a material in which the surface of the fiber is metal-plated. A typical method of metal plating the surface of a fiber is to support catalyst particles of a few nm in size on the surface of the fiber and plate the surface of the fiber using the catalyst particles as a core.
[0003] Patent Document 1 discloses a method for producing plated fibers. Specifically, the method includes a first step of applying a metal particle-containing polyester elastomer resin solution to the surface of an organic polymer fiber, a second step of drying the organic polymer fiber to form a sheath structure, and a third step of immersing the organic polymer fiber with the sheath structure formed in an electroless plating solution to form a metal coating. The metal particles in the sheath structure act as a catalyst for the plating metal. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2017-52975 A Summary of the Invention [Problem to be solved by the invention]
[0005] In order to increase the electrical conductivity of plated fibers, it is preferable that the fiber surface is covered as uniformly as possible with a metal plating. In order to uniformly cover the fiber surface with a metal plating, it is necessary to improve the deposition properties of the metal plating. However, in conventional manufacturing methods, it is difficult to uniformly cover the fiber surface with a metal plating because the deposition properties of the metal plating are insufficient.
[0006] The present invention has been made in view of the problems inherent in the conventional techniques, and an object of the present invention is to provide a plated carbon material having improved deposition properties and uniformity of a metal plating, and a method for producing the same. [Means for solving the problem]
[0007] A plated carbon material according to a first aspect of the present invention comprises a carbon material consisting of at least one of carbon fibers and organic fibers mainly composed of an organic polymer having a carbon skeleton, a particulate electroless plating catalyst supported on the surface of the carbon material, metal fine particles supported on the surface of the carbon material and having an average particle diameter smaller than that of the electroless plating catalyst, and a metal plating layer provided on the surface of the carbon material and having the electroless plating catalyst and the metal fine particles therein.
[0008] A method for producing a plated carbon material according to a second aspect of the present invention includes the steps of preparing a carbon material consisting of at least one of carbon fibers and organic fibers mainly composed of an organic polymer having a carbon skeleton, supporting a particulate electroless plating catalyst on the surface of the carbon material, supporting metal fine particles having an average particle size smaller than that of the electroless plating catalyst on the surface of the carbon material, and forming a metal plating layer by electroless plating on the carbon material supporting the electroless plating catalyst and the metal fine particles on its surface. Effect of the Invention
[0009] According to the present invention, it is possible to provide a plated carbon material with improved deposition properties and uniformity of metal plating, and a method for producing the same. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a cross-sectional view that illustrates an example of a plated carbon material according to an embodiment of the present invention. [Figure 2A] FIG. 2 is a schematic diagram showing a state in which an electroless plating catalyst is supported on the surface of a carbon material in a method for producing a plated carbon material. [Figure 2B] FIG. 2 is a schematic diagram showing a state in which an electroless plating catalyst and metal fine particles are supported on the surface of a carbon material in a method for producing a plated carbon material. [Figure 2C] FIG. 2 is a schematic diagram showing a state in which a metal plating layer is formed on a carbon material carrying an electroless plating catalyst and metal fine particles on its surface in a method for producing a plated carbon material. [Diagram 3] 1 is a photograph showing the results of observation, using a transmission electron microscope, of the vicinity of the boundary between the carbon material and the epoxy resin in the carbon material supporting palladium particles as an electroless plating catalyst and ruthenium particles as metal fine particles in Reference Example 1. [Figure 4] 1 is a photograph showing the results of observation, using a transmission electron microscope, of the vicinity of the boundary between the carbon material and the epoxy resin in the carbon material supporting only palladium particles as an electroless plating catalyst in Reference Example 1. [Figure 5A] 1 is a photograph showing the results of observation, using a transmission electron microscope, of the vicinity of the boundary between the carbon material and the epoxy resin in the carbon material supporting palladium particles as an electroless plating catalyst and ruthenium particles as metal fine particles in Reference Example 2. [Figure 5B] 5B is a photograph showing an elemental map of the distribution of palladium in the carbon material of FIG. 5A observed using an energy dispersive X-ray spectrometer. [Figure 5C] 5B is a photograph showing an elemental map of the distribution of ruthenium in the carbon material of FIG. 5A observed using an energy dispersive X-ray spectrometer. [Figure 6] 5B is a photograph showing the result of observing the carbon material of FIG. 5A at a further magnification. [Figure 7A]1 is a photograph showing the results of observing, using a digital microscope, the surface of the carbon material of Example 1, in which the Pd—Ru-supporting carbon material was copper-plated. [Figure 7B] 1 is a photograph showing the results of observing, with a scanning electron microscope, the surface of the carbon material of Example 1, in which the Pd—Ru-supporting carbon material was copper-plated. [Figure 7C] 1 is a photograph showing the results of observing, with a scanning electron microscope, a cross section of the carbon material of Example 1, in which the Pd—Ru-supporting carbon material was copper-plated. [Figure 8A] 1 is a photograph showing the results of observing, using a digital microscope, the surface of the carbon material of Comparative Example 1, in which a Pd-supported carbon material was copper-plated. [Figure 8B] 1 is a photograph showing the results of observing, with a scanning electron microscope, the surface of the carbon material of Comparative Example 1, in which a Pd-supported carbon material was copper-plated. [Figure 8C] 1 is a photograph showing the results of observing, with a scanning electron microscope, a cross section of the carbon material of Comparative Example 1 in which a Pd-supporting carbon material was copper-plated. [Figure 9] 1 is a photograph showing the results of observing, with a scanning electron microscope, the surface of the carbon material of Example 2, in which the Pd—Ru-supporting carbon material was copper-plated. [Figure 10] 1 is a photograph showing the results of observing, with a scanning electron microscope, the surface of the carbon material of Comparative Example 2, in which a Pd-supported carbon material was copper-plated. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, the plated carbon material and the method for manufacturing the plated carbon material according to the present embodiment will be described in detail with reference to the drawings. Note that the dimensional ratios in the drawings are exaggerated for the convenience of explanation and may differ from the actual ratios.
[0012] [Plated carbon materials] As shown in FIG. 1, the plated carbon material 1 according to this embodiment includes a fibrous carbon material 2, an electroless plating catalyst 3 and metal fine particles 4 supported on a surface 2a of the carbon material 2, and a metal plating layer 5 provided on the surface 2a of the carbon material 2.
[0013] In the plated carbon material 1, the carbon material 2 is a fiber made of at least one of carbon fiber and organic fiber mainly composed of an organic polymer having a carbon skeleton. The carbon fiber that can be used as the carbon material 2 is not particularly limited, but can be at least one of PAN-based carbon fiber and pitch-based carbon fiber. The organic fiber that can be used as the carbon material 2 is not particularly limited as long as it is mainly composed of an organic polymer having a carbon skeleton, but can be at least one selected from the group consisting of polyethylene terephthalate (PET) fiber, polypropylene fiber, nylon fiber, acrylic fiber, aramid fiber, and polyarylate fiber. The shape of the carbon material 2 is not particularly limited as long as it is fibrous. The components contained in the carbon material 2 can also be freely selected.
[0014] In the plated carbon material 1, a particulate electroless plating catalyst 3 is supported on the surface 2a of the carbon material 2. As described below, since the metal plating layer 5 is formed by an electroless plating method, the electroless plating catalyst 3 is necessary to promote the oxidation reaction of a reducing agent contained in an electroless plating solution. Therefore, by supporting the electroless plating catalyst 3 on the surface 2a of the carbon material 2, the film-forming property and uniformity of the metal plating layer 5 on the surface 2a of the carbon material 2 can be improved.
[0015] The electroless plating catalyst 3 may be any material that can promote the oxidation reaction of the reducing agent contained in the electroless plating solution. However, the electroless plating catalyst 3 is preferably composed mainly of at least one metal selected from the group consisting of iron, nickel, cobalt, and platinum group elements. Specifically, the electroless plating catalyst 3 preferably contains 50 mol % or more of these metals, more preferably 80 mol % or more. The platinum group element that can be used for the electroless plating catalyst 3 may be at least one selected from the group consisting of ruthenium, rhodium, palladium, osmium, iridium, and platinum. The electroless plating catalyst 3 may also be an alloy of at least one metal selected from the group consisting of iron, nickel, cobalt, and platinum group elements with another metal.
[0016] The particle size of the electroless plating catalyst 3 supported on the surface 2a of the carbon material 2 is not particularly limited. However, it is preferable that the average particle size of the electroless plating catalyst 3 is 5 nm or less. By reducing the particle size of the electroless plating catalyst 3, the specific surface area of the electroless plating catalyst 3 increases, which promotes the oxidation reaction of the reducing agent contained in the electroless plating solution and makes it possible to improve the deposition property of the plating metal. The lower limit of the average particle size of the electroless plating catalyst 3 is not particularly limited, but can be, for example, 1 nm. The particle size of the electroless plating catalyst 3 can be measured by observing the plated carbon material 1 with a transmission electron microscope (TEM).
[0017] In the plated carbon material 1, metal fine particles 4 are supported on the surface 2a of the carbon material 2 in addition to the electroless plating catalyst 3. The metal fine particles 4 may be in direct contact with the surface 2a of the carbon material 2, may be in direct contact with the particles of the electroless plating catalyst 3, or may be in direct contact with both the surface 2a of the carbon material 2 and the particles of the electroless plating catalyst 3. The metal fine particles 4 may be arranged so as to cover the surfaces of the particles of the electroless plating catalyst 3 attached to the surface 2a of the carbon material 2. The metal fine particles 4 may be distributed in a layer shape so as to cover the surfaces of the particles of the electroless plating catalyst 3 attached to the surface 2a of the carbon material 2. By supporting the metal fine particles 4 on the surface 2a of the carbon material 2, the surface 2a of the carbon material 2 and the electroless plating catalyst 3 are easily attached to each other, so that the plating metal is easily deposited on the surface 2a of the carbon material 2. Therefore, it is possible to uniformly form a metal plating layer 5 on the surface 2a of the carbon material 2.
[0018] The detailed reason why the electroless plating catalyst 3 is more likely to adhere to the surface 2a of the carbon material 2 by supporting the metal fine particles 4 is unclear. However, as described below, in the absence of the metal fine particles 4, the proportion of the electroless plating catalyst 3 that is detached from the surface 2a of the carbon material 2 increases, and the number of areas on the surface 2a of the carbon material 2 where the metal plating layer 5 is not formed increases. In contrast, in the presence of the metal fine particles 4, the proportion of the electroless plating catalyst 3 that is detached from the surface 2a of the carbon material 2 decreases, and thus plating deposition properties are improved, making it easier for the metal plating layer 5 to be formed uniformly on the surface 2a of the carbon material 2.
[0019] Furthermore, the metal microparticles 4 can exert a catalytic action similar to that of the electroless plating catalyst 3 due to the constituent metal. In other words, the metal microparticles 4 can exert a catalytic action serving as a plating nucleus, similar to the electroless plating catalyst 3, due to the constituent metal. Therefore, with an increase in the electroless plating catalyst 3 and the metal microparticles 4 functioning as catalytic particles, not only the plating deposition property but also the uniformity of the metal plating layer 5 can be improved.
[0020] The metal constituting the metal microparticles 4 is not particularly limited as long as it can exert the above-mentioned effect. However, the metal microparticles 4 are preferably mainly composed of at least one metal selected from the group consisting of iron, nickel, cobalt, and platinum group elements. Specifically, the metal microparticles 4 preferably contain 50 mol % or more of these metals, and more preferably contain 80 mol % or more. The platinum group element that can be used for the metal microparticles 4 can be at least one selected from the group consisting of ruthenium, rhodium, palladium, osmium, iridium, and platinum. The metal microparticles 4 may also be an alloy of at least one metal selected from the group consisting of iron, nickel, cobalt, and platinum group elements with another metal.
[0021] The average particle diameter of the metal fine particles 4 is preferably smaller than that of the electroless plating catalyst 3. This allows the electroless plating catalyst 3 to adhere easily to the surface 2a of the carbon material 2. Furthermore, the metal fine particles 4 themselves can exhibit catalytic action as the plating nucleus, which can improve the plating deposition property and the uniformity of the metal plating layer 5. However, the average particle diameter of the metal fine particles 4 is preferably 2 nm or less. By reducing the particle diameter of the metal fine particles 4, the specific surface area of the metal fine particles 4 increases, which makes it possible to improve the deposition property of the plating metal. The lower limit of the average particle diameter of the metal fine particles 4 is not particularly limited, but can be, for example, 0.5 nm. The particle diameter of the metal fine particles 4 can be measured by observing the plated carbon material 1 with a transmission electron microscope (TEM).
[0022] The electroless plating catalyst 3 and the metal fine particles 4 may be made of different metals. For example, when the electroless plating catalyst 3 is made of palladium, the metal fine particles 4 may be made of ruthenium. However, it is preferable that the metals of the electroless plating catalyst 3 and the metal fine particles 4 are appropriately adjusted depending on the constituent metals of the metal plating layer 5.
[0023] The plated carbon material 1 has a metal plating layer 5 on the surface 2a of the carbon material 2. With this configuration, the metal plating layer 5 acts as a conductive site. Therefore, the plated carbon material 1 can be used as a conductive material and an electromagnetic wave shielding material. Furthermore, since the carbon material 2 itself has conductivity, the carbon material 2 acts as a conductive site in addition to the metal plating layer 5, so that a plated carbon material 1 having high conductivity can be obtained.
[0024] The metal plating layer 5 is formed by an electroless plating method as described later, and is further formed by at least the catalytic action of the electroless plating catalyst 3. When the metal fine particles 4 are made of a metal having catalytic action, the metal plating layer 5 is also formed by the catalytic action of the metal fine particles 4. As described above, the electroless plating catalyst 3 is supported so as to be in close contact with the surface 2a of the carbon material 2 by the action of the metal fine particles 4. Furthermore, the metal fine particles 4 may also be supported so as to be in contact with the surface 2a of the carbon material 2, or may be disposed so as to cover the surface of the particles of the electroless plating catalyst 3. Therefore, the metal plating layer 5 is formed so as to be in direct contact with the surface 2a of the carbon material 2, and further has both the electroless plating catalyst 3 and the metal fine particles 4 inside.
[0025] The metal plating layer 5 is formed by the action of the electroless plating catalyst 3 that is in close contact with at least the surface 2a of the carbon material 2. Furthermore, when the metal fine particles 4 are made of a metal having catalytic action, the metal plating layer 5 is also formed by the catalytic action of the metal fine particles 4. The action of the electroless plating catalyst 3 and the metal fine particles 4 improves the deposition of the plating metal, so that the metal plating layer 5 can be formed with a substantially uniform thickness over the entire surface 2a of the carbon material 2.
[0026] The metal constituting the metal plating layer 5 is not particularly limited. However, the metal plating layer 5 preferably contains at least one metal selected from the group consisting of copper, silver, gold, nickel, chromium, tin, and zinc as a main component. Specifically, the metal plating layer 5 preferably contains 50 mol % or more of such metal, and more preferably contains 80 mol % or more. When the metal plating layer 5 contains such a metal as a main component, the conductivity of the metal plating layer 5 can be further increased.
[0027] The thickness of the metal plating layer 5 is not particularly limited, but is preferably 0.2 μm or more, and more preferably 0.4 μm or more. With this configuration, the electrical conductivity of the metal plating layer 5 is ensured, while the adhesion between the metal plating layer 5 and the surface 2a of the carbon material 2 is increased, and flexibility of the plated carbon material 1 can be obtained. The upper limit of the thickness of the metal plating layer 5 is not particularly limited, but can be, for example, 3.0 μm or less.
[0028] Thus, the plated carbon material 1 of this embodiment includes a carbon material 2 made of at least one of carbon fibers and organic fibers mainly composed of an organic polymer having a carbon skeleton. The plated carbon material 1 further includes a particulate electroless plating catalyst 3 supported on the surface 2a of the carbon material 2, and metal fine particles 4 supported on the surface 2a of the carbon material 2 and having an average particle size smaller than that of the electroless plating catalyst 3. The plated carbon material 1 includes a metal plating layer 5 provided on the surface 2a of the carbon material 2 and having the electroless plating catalyst 3 and the metal fine particles 4 therein. Since the plated carbon material 1 supports the electroless plating catalyst 3 and the metal fine particles 4 on the surface 2a of the carbon material 2, the electroless plating catalyst 3 is in close contact with the surface 2a of the carbon material 2. Furthermore, when the metal fine particles 4 are made of a metal having catalytic action, the metal fine particles themselves can exert catalytic action. As a result, the deposition property of the plating metal is improved, and the metal plating layer 5 of a substantially uniform thickness can be formed on the entire surface 2a of the carbon material 2.
[0029] The plated carbon material 1 can be used as a conductive material and an electromagnetic wave shielding material because it has high conductivity due to the action of the metal plating layer 5. Furthermore, the plated carbon material 1 can also be used to form conductive woven and nonwoven fabrics.
[0030] [Method of manufacturing plated carbon material] Next, a method for producing a plated carbon material according to this embodiment will be described.
[0031] In the manufacturing method of this embodiment, first, a carbon material 2 made of at least one of carbon fiber and organic fiber mainly composed of an organic polymer having a carbon skeleton is prepared. As the carbon material 2, the above-mentioned materials can be used.
[0032] Next, a particulate electroless plating catalyst 3 is supported on the surface 2a of the carbon material 2. The method for supporting the electroless plating catalyst 3 is not particularly limited, and can be, for example, a wet method or a supercritical (subcritical) fluid treatment method.
[0033] The electroless plating catalyst 3 can be supported by the wet method through the following steps. Specifically, the steps include a degreasing step for removing oil and fat components adhering to the surface of the carbon material 2 and improving wettability, an etching step for chemically roughening the surface 2a of the carbon material 2, a catalyst step for adsorbing the catalytic metal constituting the electroless plating catalyst 3, and an accelerator step for activating the catalytic metal through an oxidation-reduction reaction. Through these steps, the particulate electroless plating catalyst 3 can be supported on the surface 2a of the carbon material 2, as shown in FIG. 2A.
[0034] The electroless plating catalyst 3 can be supported by the supercritical (subcritical) fluid treatment method through the following steps. Specifically, first, the carbon material 2 is immersed in a supercritical fluid or subcritical fluid (e.g., supercritical carbon dioxide) containing an organometallic complex of a plating catalyst metal. This causes the organometallic complex of the plating catalyst metal to adhere to the surface of the carbon material 2. Then, the carbon material 2 to which the organometallic complex is attached is heat-treated, whereby the particulate electroless plating catalyst 3 can be supported on the surface 2a of the carbon material 2, as shown in FIG. 2A.
[0035] 2B, metal fine particles 4 having an average particle size smaller than that of the electroless plating catalyst 3 are supported on the surface of the carbon material 2. The method of supporting the metal fine particles 4 is not particularly limited, but for example, a coating device such as a vacuum electron dyeing device can be used. By using such a coating device, the metal fine particles 4 can be attached so as to cover the surfaces of the particles of the electroless plating catalyst 3 attached to the surface 2a of the carbon material 2.
[0036] 2C, a metal plating layer 5 is formed by electroless plating on the carbon material 2 supporting the electroless plating catalyst 3 and the metal fine particles 4 on the surface 2a. Specifically, the carbon material 2 supporting the electroless plating catalyst 3 and the metal fine particles 4 is immersed in an electroless plating solution to perform an electroless plating process, thereby forming the metal plating layer 5. At this time, the temperature of the electroless plating solution can be set to 40° C. to 100° C., and the immersion time can be set to 10 minutes to 90 minutes.
[0037] Here, when the carbon material 2 is immersed in an electroless plating solution, the reducing agent contained in the plating solution is oxidized by the catalytic action of the electroless plating catalyst 3, and electrons are released, and the metal ions in the plating solution are reduced by the electrons. As a result, the metal can be deposited on the surface 2a of the carbon material 2 as a metal plating layer 5. That is, the metal plating layer 5 is deposited with the electroless plating catalyst 3 as a nucleus. However, as described above, by supporting the metal fine particles 4, the electroless plating catalyst 3 is easily attached to the surface 2a of the carbon material 2. Furthermore, the metal fine particles 4 can exhibit a catalytic action to become the nucleus of plating, similar to the electroless plating catalyst 3, depending on the metal that constitutes it. In this way, the plating deposition property is improved by the action of the electroless plating catalyst 3 and the metal fine particles 4, and the metal plating layer 5 can be uniformly formed on the surface 2a of the carbon material 2.
[0038] Then, the carbon material 2 on which the metal plating layer 5 has been formed is washed with ion-exchanged water or the like, and then dried, whereby the plated carbon material 1 can be obtained.
[0039] As described above, the method for producing the plated carbon material 1 of this embodiment includes the steps of preparing a carbon material 2 made of at least one of carbon fibers and organic fibers mainly composed of an organic polymer having a carbon skeleton, supporting a particulate electroless plating catalyst 3 on the surface 2a of the carbon material 2, supporting metal fine particles 4 having an average particle size smaller than that of the electroless plating catalyst 3 on the surface 2a of the carbon material 2, and forming a metal plating layer 5 by an electroless plating method on the carbon material 2 supporting the electroless plating catalyst 3 and the metal fine particles 4 on the surface 2a. In this production method, the electroless plating catalyst 3 and the metal fine particles 4 supported in close contact with the surface 2a of the carbon material 2 serve as nuclei for plating, thereby improving plating deposition properties and enabling the metal plating layer 5 to be uniformly formed on the surface 2a of the carbon material 2. EXAMPLES
[0040] Hereinafter, the present embodiment will be described in more detail with reference to examples, comparative examples and reference examples, but the present embodiment is not limited to these examples and reference examples.
[0041] [Reference example 1] First, a polyethylene terephthalate (PET) nonwoven fabric was prepared as a carbon material. The PET fibers in the polyethylene terephthalate nonwoven fabric had a fiber diameter of about 15 μm and a thickness of about 0.5 mm.
[0042] Next, palladium particles were supported on the surface of the carbon material by a supercritical fluid treatment method. Specifically, palladium particles were supported on the surface of the carbon material according to the plating pretreatment method described in Japanese Patent No. 5649984. In detail, first, a palladium organometallic complex was dissolved in carbon dioxide in a supercritical state under conditions of a temperature of 100 to 130°C and a pressure of 12 to 15 MPa. Next, the carbon material was put into the carbon dioxide in a supercritical state in which the palladium organometallic complex was dissolved, and immersed for 30 minutes to support palladium on the carbon material. Then, the carbon material was heat-treated in the air at 150°C for 1 hour to obtain a carbon material supporting palladium particles.
[0043] Next, ruthenium particles were attached to the carbon material carrying palladium particles by vacuum electron staining. Specifically, ruthenium particles were attached to the carbon material using a vacuum electron staining device (VSC4TH) manufactured by Filgen. In detail, first, ruthenium tetroxide gas adjusted to a concentration of 500 Pa was filled in the chamber of the vacuum electron staining device. Next, the carbon material carrying palladium particles was put into the chamber and held at room temperature for 1 hour, and then the carbon material was taken out of the chamber.
[0044] In this manner, a test sample was obtained, which was made of a carbon material carrying on its surface palladium particles as an electroless plating catalyst and ruthenium particles as fine metal particles.
[0045] Epoxy resin was applied to the surface of the test sample thus obtained and solidified. Then, the cross section of the test sample in the cross-sectional direction was processed by focused ion beam (FIB) and then sliced to a thickness of about 50 to 100 nm. The sliced test sample was then observed with a transmission electron microscope (TEM). FIG. 3 shows the result of observing the vicinity of the boundary between the carbon material and the epoxy resin in the test sample. FIG. 4 shows the result of observing the vicinity of the boundary between the carbon material and the epoxy resin in a carbon material carrying only palladium particles. Note that FIGS. 3 and 4 are photographs enlarged 300,000 times.
[0046] As shown in Figure 3, it was confirmed that the test samples carrying palladium particles and ruthenium particles had palladium particles held in a highly adherent manner on the surface of the carbon material. That is, it can be seen in Figure 3 that the palladium particles shown in black particle form are adhered to the surface of the carbon material. In contrast, as shown in Figure 4, it was confirmed that the carbon material to which ruthenium was not attached had black particles suspended in the epoxy resin. That is, it can be seen in Figure 4 that the palladium particles shown in black particle form are not adhered to the surface of the carbon material but are suspended in the epoxy resin.
[0047] It is thus apparent that by adhering metal particles to the surface of the carbon material in addition to the electroless plating catalyst, the adhesive strength between the surface of the carbon material and the particles of the electroless plating catalyst is improved.
[0048] [Reference example 2] First, PAN-based carbon fibers were prepared as the carbon material. The PAN-based carbon fibers had a fiber diameter of about 7 μm and 12,000 fibers.
[0049] Next, palladium particles were supported on the surface of the carbon material by a supercritical fluid treatment method. Specifically, as in Reference Example 1, first, a palladium organometallic complex was dissolved in carbon dioxide in a supercritical state under conditions of a temperature of 100 to 130°C and a pressure of 12 to 15 MPa. Next, the carbon material was put into the carbon dioxide in a supercritical state in which the palladium organometallic complex was dissolved, and immersed for 30 minutes to support palladium on the carbon material. Then, the carbon material was heat-treated in the air at 300°C for 1 hour to obtain a carbon material supporting palladium particles.
[0050] Next, ruthenium particles were attached to the carbon material supporting the palladium particles by vacuum electron dyeing in the same manner as in Reference Example 1. In this manner, a test sample was obtained that consisted of a carbon material supporting palladium particles as an electroless plating catalyst and ruthenium particles as metal fine particles on the surface of the carbon material.
[0051] Epoxy resin was applied to the surface of the test sample thus obtained and solidified. Then, the cross section of the test sample in the cross-sectional direction was processed by focused ion beam (FIB) and then sliced to a thickness of about 50 to 100 nm. The sliced test sample was then observed with a transmission electron microscope (TEM). FIG. 5A shows the result of observing the vicinity of the boundary between the carbon material and the epoxy resin in the test sample. FIG. 5B shows an element map of the distribution of palladium observed using an energy dispersive X-ray spectroscopy (EDS) detector mounted on the TEM. FIG. 5C shows an element map of the distribution of ruthenium observed using an energy dispersive X-ray spectroscopy detector. Note that FIGS. 5A to 5C are photographs magnified 300,000 times.
[0052] From Figs. 5A to 5C, it can be seen that the ruthenium particles are distributed in layers so as to cover the palladium particles attached to the surface of the carbon fiber. The thickness of the ruthenium particles distributed in layers was about 15 nm. Fig. 6 is a photograph of the test sample shown in Fig. 5A, enlarged 600,000 times. From Fig. 6, it can be seen that very fine ruthenium particles with a particle diameter of 1 nm or less are present almost uniformly on the surface of the carbon material. It can also be seen that the particle diameter of the ruthenium particles is smaller than that of the palladium particles.
[0053] [Example 1, Comparative Example 1] First, PAN-based carbon fibers were prepared as the carbon material. The PAN-based carbon fibers had a fiber diameter of about 7 μm and 12,000 fibers.
[0054] Next, palladium particles were supported on the surface of the carbon material by a supercritical fluid treatment method. Specifically, as in Reference Example 1, first, a palladium organometallic complex was dissolved in carbon dioxide in a supercritical state under conditions of a temperature of 100 to 130°C and a pressure of 12 to 15 MPa. Next, the carbon material was put into the carbon dioxide in a supercritical state in which the palladium organometallic complex was dissolved, and immersed for 30 minutes to support palladium on the carbon material. Then, the carbon material was heat-treated in the air at 300°C for 1 hour to obtain a carbon material supporting palladium particles.
[0055] Next, in the same manner as in Reference Example 1, ruthenium particles were attached to the carbon material supporting the palladium particles by the vacuum electron dyeing method.
[0056] In this way, a Pd-Ru supported carbon material was obtained in which palladium particles as an electroless plating catalyst and ruthenium particles as metal fine particles were supported on the surface of the carbon material. The amount of palladium supported in the Pd-Ru supported carbon material was 99.2 ppm.
[0057] Furthermore, a Pd-supported carbon material was obtained by the same method as above, which supported only palladium particles without supporting ruthenium particles, and the amount of palladium supported in the Pd-supported carbon material was 99.2 ppm.
[0058] Next, the Pd-Ru-supported carbon material and the Pd-supported carbon material obtained as described above were subjected to copper plating. Specifically, the Pd-Ru-supported carbon material and the Pd-supported carbon material were immersed in an electroless plating bath (formalin bath) containing copper ions. At this time, the Pd-Ru-supported carbon material was immersed in the electroless plating bath for 3 minutes, and the Pd-supported carbon material was immersed in the electroless plating bath for 6 minutes. The plating bath conditions were a copper concentration of 2.5 g / L, a NaOH concentration of 8.0 g / L, a formalin concentration of 3.0 g / L, and a bath temperature of 45°C. The plated carbon material was washed with ion-exchanged water and then dried to obtain a copper-plated carbon material.
[0059] The carbon material obtained by copper plating the Pd--Ru supported carbon material was used as test sample 1 of Example 1, and the carbon material obtained by copper plating the Pd supported carbon material was used as test sample 2 of Comparative Example 1.
[0060] FIG. 7A shows a photograph of the test sample 1 of Example 1, magnified 200 times using a digital microscope. FIG. 7B shows a photograph of the surface of the test sample 1, magnified 1000 times using a scanning electron microscope (SEM). FIG. 7C shows a photograph of the cross section of the test sample 1, magnified 5000 times using a scanning electron microscope. The photograph in FIG. 7C was observed with a scanning electron microscope in a state in which the cross section was exposed with a cross-section polisher after epoxy resin was applied to the test sample 1 and solidified. In FIG. 7C, the streaky lines extending vertically from the surface of the carbon fiber were generated by processing during ion polishing.
[0061] As shown in FIGS. 7A to 7C, in test sample 1, a copper plating film is formed on substantially the entire surface of the carbon material, and it can be confirmed that the thickness is also substantially uniform.
[0062] FIG. 8A shows a photograph of the test sample 2 of Comparative Example 1, magnified 200 times using a digital microscope. FIG. 8B shows a photograph of the surface of the test sample 2, magnified 1000 times using a scanning electron microscope (SEM). FIG. 8C shows a photograph of the cross section of the test sample 2, magnified 5000 times using a scanning electron microscope. The photograph in FIG. 8C was observed with a scanning electron microscope in a state in which an epoxy resin was applied to the test sample 2 and solidified, and then the cross section was exposed with a cross-section polisher. In FIG. 8C, the streaky lines extending vertically from the surface of the carbon fiber were generated by processing during ion polishing.
[0063] 8A to 8C, it can be seen that the thickness of the copper plating film is thin overall and the areas where the plating is applied are very sparse in Test Sample 2. It can also be seen that Test Sample 2 is inferior to Test Sample 1 in terms of plating deposition properties and uniformity of the metal plating layer, even though the carbon material was immersed in the electroless plating solution for twice as long.
[0064] Here, from the above-mentioned Reference Example 1, it is found that by attaching metal fine particles to the surface of the carbon material in addition to the electroless plating catalyst, the adhesion between the surface of the carbon material and the particles of the electroless plating catalyst is improved. Furthermore, from Reference Example 2, it is found that very fine metal fine particles with a particle diameter of 1 nm or less are substantially uniformly present on the surface of the carbon material. And, from Example 1, it is found that by attaching metal fine particles in addition to the electroless plating catalyst, a metal plating layer is formed with a substantially uniform thickness on the entire surface of the carbon material. In this way, by attaching both the electroless plating catalyst and the metal fine particles to the surface of the carbon material, the probability of the catalyst particles being detached during the plating process is reduced, so that it is possible to improve the plating deposition property. In addition, since both the palladium particles and the ruthenium fine particles exhibit catalytic action as the nucleus of plating, and further, these particles are uniformly distributed on the surface of the carbon material, it is possible to improve not only the plating deposition property but also the uniformity of the metal plating layer.
[0065] [Example 2, Comparative Example 2] A Pd-Ru-supported carbon material and a Pd-supported carbon material were obtained by the same method as in Example 1 and Comparative Example 1, except that the amount of palladium supported was changed to 1050 ppm. Then, the obtained Pd-Ru-supported carbon material and Pd-supported carbon material were copper-plated by the same method as in Example 1 to obtain carbon materials. The immersion time of the carbon material in the electroless plating solution was 3 minutes in both cases. The carbon material obtained by copper plating the Pd-Ru-supported carbon material was used as test sample 3 of Example 2, and the carbon material obtained by copper plating the Pd-supported carbon material was used as test sample 4 of Comparative Example 2.
[0066] FIG. 9 shows a photograph of Test Sample 3 of Example 2, magnified 1000 times using a digital microscope. FIG. 10 shows a photograph of Test Sample 4 of Comparative Example 2, magnified 1000 times using a digital microscope. From FIG. 9 and FIG. 10, it can be seen that, for the same plating time, when ruthenium fine particles were supported, the carbon material was copper plated over almost the entire surface, whereas when ruthenium fine particles were not supported, the copper plating was sparse. Although the difference was not as significant as in the case of Test Samples 1 and 2, where the amount of supported palladium was small, it can be seen that the deposition and uniformity of the copper plating are further improved by supporting ruthenium fine particles.
[0067] Thus, it is understood that the carbon material of this embodiment, by supporting metal fine particles, improves the deposition property and uniformity of the metal plating layer regardless of the amount of electroless plating catalyst.
[0068] Although the present embodiment has been described above, the present embodiment is not limited to this, and various modifications are possible within the scope of the gist of the present embodiment. [Explanation of symbols]
[0069] 1. Plated carbon materials 2 Carbon materials 2a Carbon surface 3. Electroless plating catalyst 4 Metal fine particles 5 Metal plating layer
Claims
1. A carbon material including at least one of carbon fiber and organic fiber mainly composed of an organic polymer having a carbon skeleton; A particulate electroless plating catalyst supported on the surface of the carbon material; Metal fine particles supported on a surface of the carbon material and having an average particle size smaller than that of the electroless plating catalyst; a metal plating layer provided on a surface of the carbon material and having the electroless plating catalyst and the metal fine particles therein; A plated carbon material comprising:
2. 2. The plated carbon material according to claim 1, wherein the electroless plating catalyst and the metal fine particles are mainly composed of at least one metal selected from the group consisting of iron, nickel, cobalt and platinum group elements.
3. 3. The plated carbon material according to claim 1, wherein the electroless plating catalyst and the metal fine particles are made of different metals.
4. 3. The plated carbon material according to claim 1, wherein the electroless plating catalyst has an average particle size of 5 nm or less, and the metal fine particles have an average particle size of 2 nm or less.
5. 3. The plated carbon material according to claim 1, wherein the metal plating layer contains at least one metal selected from the group consisting of copper, silver, gold, nickel, chromium, tin and zinc as a main component.
6. A step of preparing a carbon material including at least one of carbon fibers and organic fibers mainly composed of an organic polymer having a carbon skeleton; supporting a particulate electroless plating catalyst on a surface of the carbon material; supporting metal fine particles having an average particle size smaller than that of the electroless plating catalyst on a surface of the carbon material; forming a metal plating layer by an electroless plating method on the carbon material having the electroless plating catalyst and the metal fine particles supported on the surface thereof; The present invention relates to a method for producing a plated carbon material.
Citation Information
Patent Citations
Plated fiber and production method thereof
JP2017052975A